Continuity of Music Education during the Covid-19 Pandemic in the Society 5.0 Era - Richard Junior Kapoyos; Laura Megawaty Manalu (Journal of International Conference Proceedings (JICP), 2021)
Education in Indonesia from elementary to college has experienced a change in the learning process caused by the Covid-19 pandemic, one of them is learning in the field of music, which was originally offline and later because of this pandemic learning was carried out online. The government's policy is to carry out all activities at home, in order to cut the chain of the spread of the Covid-19 pandemic, which is a tough test for music educators. These changes occur because of the community's efforts to adapt to new needs, conditions, and conditions that arise in line with the growth of society. Not finished with the issue of the Industrial Revolution 4.0, now people are faced with back with the issue of society 5.0, objects and all existing social orders integrated with the virtual world. The purpose of this research to determine continuity of music education during the Covid-19 pandemic in the era of the Society 5.0. The method used is literature review, namely using various sources of reference both from research results and from the thoughts of other authors. The results of this conceptual research are expected to provide local wisdom values because music is one of the important elements for society in facing a changing era.